Advances in management accounting. 32 - Burney, Laurie L. (Emerald Publishing Limited, 2020)
Advances in Management Accounting (AIMA) is a publication of quality applied research in management accounting. The journal's purpose is to publish thought-provoking articles that advance knowledge in the management accounting discipline and are of interest to both academics and practitioners. As a premier management accounting research journal, AIMA is well-poised to meet the needs of management accounting scholars. Featured in Volume 32 are articles on: Public Sector Joint Ventures; Control; Trust; Perceived Risk; Cost Stickiness; Cost Behavior; Environmental, Social, and Governance (ESG) Sustainability Performance; Information Asymmetry; Sustainability Disclosure; Corporate Social Responsibility (CSR); Asymmetric Cost Behavior; Lease Cost Stickiness; Retail Firms Cost Stickiness; Mood; Sunshine; Managerial Optimism; Asymmetric Cost Behavior; Adjustment Costs; Academic Research, Research-Practice Gap; Rigor-Relevance; Impact; Engagement; Relational Performance Measurement System; Managerial Ability; Employee Productivity; Employee Efficiency; Employee Cost; Financial Distress; Environmental Uncertainty.
Introduction; Laurie L. Burney Chapter 1: Understanding the Interactions between Control, Trust, and Perceived Risk in Public Sector Joint Ventures; Paula van Veen-Dirks and Anneke Giliam -- Chapter 2: Is Cost Stickiness Associated with Sustainability Factors?; Joanna Golden, Mark Kohlbeck and Zabihollah Rezaee -- Chapter 3: Are Operating Lease Costs Sticky for Retail Firms?; David L. Gray -- Chapter 4: A Look on the Bright Side - The Real Effect of Mood on Corporate Short-Term Resource Adjustment Decisions: Research Note; Thomas R. Loy and Sven Hartlieb -- Chapter 5: A Performance Measurement Approach to Defining and Measuring Research Relevance: Evidence from University Senior Management; Mary A. Malina and Basil P. Tucker -- Chapter 6: Managerial Ability and Employee Productivity; Dipankar Ghosh, Xuerong (Sharon) Huang and Li Sun.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Managerial accounting; Business & Economics -- Accounting -- Managerial; Management accounting & bookkeeping